Microneedles rollers as a potential device to increase ALA diffusion and PpIX production: Evaluations by wide-field fluorescence imaging and fluorescence spectroscopy - Sousa, R. Phamilla Gracielli; De Menezes, Priscila F.C.; Fujita, Alessandra K.L.; Requena, Michelle B.; Govone, Angelo Biassi; Escobar, André; De Nardi, Andrigo B. [UNESP]; Kurachi, Cristina; Bagnato, Vanderlei Salvador (SPIE, the international society for optics and photonics, 2014)
One of the limitations of topical photodynamic therapy (PDT) using 5-aminolevulinic acid (ALA) is the poor ability to penetrate biological barriers of skin and the recurrence rates in treatments. This study aimed to identify possible signs of increased diffusion of ALA-induced PpIX by fluorescence images and fluorescence spectroscopy. The research was done using in vivo porcine skin model. Before the cream application, microholes was performed with microneedles rollers in only one direction, afterward the ALA cream was applied at a 2.5cm2 area in triplicate and an occlusive dressing was placed. PpIX production was monitored using fluorescence spectroscopy collected at skin surface after 70, 100, 140, and 180 minutes of ALA incubation. About 100 fluorescence spectra of each treatment were collected, distributed by about five points for each site. Wide-field fluorescence imaging was made after 70, 90, and 170 minutes after treatment. The results obtained by imaging analysis indicated increase of the PpIX diffusion in the skin surface using the microneedles rollers (MNs) before ALA application. Circular regions of red fluorescence around the microholes were observed. In addition, the fluorescence spectra showed a greater intensity (2 times as many) in groups microneedles rollers associated. In conclusion, our data shown greater homogeneity and PpIX production in the groups pre-treated with microneedles indicating that the technique can be used to greater uniformity of PpIX production throughout the area to be treated reducing the chances of recurrent tumor as well as has potential for decreasing the time of therapy. © 2014 SPIE.
Keywords: Fluorescence spectroscopy; Homogeneity; Microneedles rollers; PpIX production; Wide-field fluorescence imaging